User Association Strategy for Energy Efficiency and Interference Mitigation of Heterogeneous Networks - Samira Achki; Layla Aziz; Fatima Gharnati; Abdellah Ait Ouahman (Advances in Materials Science and Engineering)
The necessity of the use of several mobile services increases every day. This requires the consumption of energy rates. Hence, minimizing the energy and interferences of mobile users are major concerns of Heterogeneous Networks (HetNet). This paper aims to improve the energy of mobile users by minimizing a weighted function. To consider significant weights values, we have exploited the multicriteria AHP method. The cost function represents the cost of users toward available BS. It includes the essential criteria influencing energy consumption. Moreover, we introduce an optimal user association based on their minimal cost values. Simulation results prove that the optimal method has saved more energy and reduced network interferences.